2007
DOI: 10.1093/sleep/30.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Hours of CPAP Use and Achieving Normal Levels of Sleepiness and Daily Functioning

Abstract: Our analyses suggest that a greater percentage of patients will achieve normal functioning with longer nightly CPAP durations, but what constitutes adequate use varies between different outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
633
2
23

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 886 publications
(682 citation statements)
references
References 36 publications
24
633
2
23
Order By: Relevance
“…60 Patients whose ES was resolved during treatment (ie, their ESS score reduced to < 10) used CPAP for approximately 1 hour more each night than study participants who reported experiencing residual ES (5.1 versus 4.0 hours of CPAP use per night, respectively). 60 Patients with higher depression scores have been reported to have lower compliance with CPAP, 61 and the interventions discussed below may be of particular use in this patient population as an aid to compliance.…”
Section: Confirmation Of Initial Diagnosismentioning
confidence: 90%
See 1 more Smart Citation
“…60 Patients whose ES was resolved during treatment (ie, their ESS score reduced to < 10) used CPAP for approximately 1 hour more each night than study participants who reported experiencing residual ES (5.1 versus 4.0 hours of CPAP use per night, respectively). 60 Patients with higher depression scores have been reported to have lower compliance with CPAP, 61 and the interventions discussed below may be of particular use in this patient population as an aid to compliance.…”
Section: Confirmation Of Initial Diagnosismentioning
confidence: 90%
“…Even with optimal CPAP therapy, up to half of patients with OSA have residual ES. 60 In patients compliant with CPAP therapy but who still experience ES, adjunctive pharmacologic therapy is a treatment option. Before introducing such therapy, it is important to ensure that CPAP is being used appropriately by checking the air pressure of the device and the level of patient compliance.…”
Section: Evaluation and Treatment Of Residual Esmentioning
confidence: 99%
“…Our tetraplegic population scored significantly worse than the normal sample in the activity level and intimate and sexual activity domains, but there was no difference in the total score and other three domains (Table 3). 12,13 Basic Nordic Sleep Questionnaire The BNSQ was completed by 163 participants. Tables showing the entire Table 1).…”
Section: Assessment Of Quality Of Lifementioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) device is currently considered to be the first-line treatment for OSA in adults [3]. When used properly, CPAP treatment is efficacious at reducing both subjective symptoms of OSA and cardiovascular risk [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, CPAP efficacy is limited by highly variable patient compliance to therapy. In the literature, the reported adherence to CPAP ranges from 30 to 70 % [3,6]. Thus, a significant number of patients ultimately abandon CPAP therapy.…”
Section: Introductionmentioning
confidence: 99%